Whole‐genome sequencing reveals absence of recent gene flow and separate demographic histories for Anopheles punctulatus mosquitoes in Papua New Guinea. Issue 6 (6th March 2015) - Logue, Kyle; Small, Scott T.; Chan, Ernest R.; Reimer, Lisa; Siba, Peter M.; Zimmerman, Peter A.; Serre, David
Abstract: Anopheles mosquitoes are the vectors of several human diseases including malaria. In many malaria endemic areas, several species of Anopheles coexist, sometimes in the form of related sibling species that are morphologically indistinguishable. Determining the size and organization of Anopheles populations, and possible ongoing gene flow among them is important for malaria control and, in particular, for monitoring the spread of insecticide resistance alleles. However, these parameters have been difficult to evaluate in most Anopheles species due to the paucity of genetic data available. Here, we assess the extent of contemporary gene flow and historical variations in population size by sequencing and de novo assembling the genomes of wild‐caught mosquitoes from four species of the Anopheles punctulatus group of Papua New Guinea. Our analysis of more than 50 Mb of orthologous DNA sequences revealed no evidence of contemporary gene flow among these mosquitoes. In addition, investigation of the demography of two of the An. punctulatus species revealed distinct population histories. Overall, our analyses suggest that, despite their similarities in morphology, behaviour and ecology, contemporary sympatric populations of An. punctulatus are evolving independently.